Hambatan Komunikasi dalam Mempromosikan Desa Agrowisata pada Wisatawan Asing - Darya Yurkova (Jurnal Ilmu Komunikasi, 2025)
Tamanmartani Village in Yogyakarta has great potential to attract foreign tourists, but faces communication barriers. This study identified challenges such as limited information, language barriers, different perceptions of tourism development, as well as difficulties finding local guides and managing social media. Data were collected through observation and interviews with managers, residents, and foreign tourists. Results showed three communication barriers: the manager's limited knowledge of marketing communication, promotional materials for foreign tourists, and the unfamiliarity of foreign tourists with the local culture. Overcoming these barriers is essential to support the sustainable growth of tourism businesses and improve interactions with foreign tourists.